The Relationship Of Using Twitter Social Media With Adolescent Sexual Behavior During Pandemi At SMPN 7 Samarinda - Masruroh, Siti; Pusvitha, Maria; Widianingsih, Sri; Alfiani, Syahrul; Sunarti, Sri; Amalia, Nida (Jurnal Ilmu Kesehatan, 2022)
Adolescent sexual behavior is a sexual activity carried out by adolescents with their partners to fulfill their desires, but this problem is considered common to society so that this case is increasing every year. The purpose of this study was to analyze the relationship between the use of Twitter social media and adolescent sexual behavior during the pandemic at SMPN 7 Samarinda. The method in this study used a cross-sectional design with a total of 97 respondents in classes VII and VIII. The research instrument used a questionnaire in the form of Google Fromulir. The result of this study is that there is no relationship between the use of social media Twitter with adolescent sexual behavior during the pandemic at SMPN 7 Samarinda. Twitter presents trending topics that are positive so that many teenagers access it, which can have a positive impact on adolescent behavior. Keywords: Twitter Social Media Use, Sexual Behavior, Teenagers.